Development of a hybrid (solid state/gas) femtosecond laser system of multiterawatt peak power - Losev V.; Alekseev S.; Ivanov N.; Kovalchuk B.; Mikheev L.; Mesyats G. A. Gennady Andreyevich; Panchenko Yu.; Ratakhin N.; Yastremsky A. (2010, 2010)
В фонде НТБ ТПУ отсутствует